The Choice Of An Optimal Nonsteroidal Anti-Inflammatory Agent For Relieving Pain In Diseases Of The Temporomandibular Joint. - Usmonkulov Shakhboz Zafarovich; Islamova Nilufar Bustanovna; Toreniyazov Akilbek Polatbekovich; Nasimov Ozod Jamshidovich (Genius Journals, 2024)
During the clinical study, a sociological survey was conducted by interviewing 98 patients of various age groups who were treated on an outpatient basis at the Regional Dental Polyclinic of Samarkand with temporomandibular joint pathologies. The purpose of our study was to study the features of their use of nonsteroidal anti-inflammatory drugs to relieve pain in diseases of the temporomandibular joint.
Keywords: pain syndrome; nonsteroidal anti-inflammatory drugs; diseases of the temporomandibular joint.